Validation of a co-simulation approach for hydraulic percussion units applied to a hydraulic hammer. (May 2019) - Andersson, H.; Simonsson, K.; Hilding, D.; Schill, M.; Sigfridsson, E.; Leidermark, D.
Highlights: Experimental validation of a co-simulation approach for hydraulic percussion units has successfully been conducted. Very good correlation to the experimental data was found. Elastic bodies were successfully used for a correct representation of the stress wave propagation in the structural components. A parameter study confirms that a correct response is obtained from a parameter change in the simulation model. Abstract: In this study, a previously developed co-simulation approach has been adopted to simulate the responses of an existing hydraulic hammer product. This approach is based on a 1D system model representing the fluid components and a 3D finite element model representing the structural parts of the hydraulic hammer. The simulation model was validated against four experiments with different running conditions. The corresponding set-ups were analysed using the co-simulation method in order to evaluate the overall responses. A parameter study was also performed involving the working pressure and the restrictor diameter, with the objective to validate that a parameter change in the simulation model will affect the input and output power in the same direction as in the experiments. The experimental responses used in the validation were time history data of fluid pressure, component position and acceleration, and structural stresses. The experiments result in high frequency and high amplitude excitations of the hydraulic hammer and thus require a model with a high resolution of the model dynamics. The conclusion of the validation is that the simulation model is able to replicate the experimental responses with high accuracy including the high frequency dynamics. The favourable outcome of the validation makes the described co-simulation approach promising as an efficient tool for a wide range of other applications where short time duration mechanisms need to be studied.